Vitamin D Receptor Polymorphisms Predispose to Primary Biliary Cirrhosis and Severity of the Disease in Polish Population. (29th May 2012) - Kempińska-Podhorecka, Agnieszka; Wunsch, Ewa; Jarowicz, Tomasz; Raszeja-Wyszomirska, Joanna; Loniewska, Beata; Kaczmarczyk, Mariusz; Milkiewicz, Małgorzata; Milkiewicz, Piotr
Abstract : Primary biliary cirrhosis (PBC) is a chronic cholestatic liver condition characterized by the immune-mediated damage of the intrahepatic bile ducts. Polymorphisms of vitamin D receptor (VDR) are considered to contribute to its pathogenesis however their incidence varies in different populations and their potential association with the course of the disease has not been studied. In this paper we investigated the incidence and correlation of three VDR polymorphisms ( BsmI, ApaI or TaqI ) with various clinical, biochemical, and serological factors in a homogenous group of 143 Caucasian patients with PBC. Control group comprises 306 DNA samples from umbilical cord blood of healthy newborn children. When compared to controls, we observed a significant dominance of the b allele in the BsmI (OR = 1.69 [1.27–2.24]; P = 0.0003 ) and t allele in the TaqI (OR = 0 .62 [0.47–0.82], P = 0.0001 ) in patients with PBC. Moreover the BsmI and TaqI polymorphisms were associated with the presence of advanced fibrosis/liver cirrhosis at the diagnosis of PBC. Pairwise linkage disequilibrium (LD) calculations proved that the analyzed SNPs are within an LD block (100% of LDs were D ' > 0.9 ). Our study showed, for the first time, that the analyzed polymorphisms of VRD may exert an effect on a natural history of PBC.